Remnants of Atlantic Forest in The APP of the Dam of Morrinhos in Poções – Bahia (Research, Society and Development, 2023)
The use of GIS in mapping studies of land use and vegetation cover is an important instrument for planning and managemen of the physical environment. This work aimed to present the dynamics of native vegetation in the area of permanent protection - APP of the Morrinhos Dam in Poções - Bahia, in the years 2008 and 2013. The processes used in the study were conducted in QGis. The definition of the perimeter of the accumulation area of the dam of Morrinhos. The results show the evolution of deforestation in the municipality of Poções and vegetation cover on the APP of the dam of Morrinhos between 2008 and 2013. The results observed in this work show high rate of deforestation and forest fragmentation of the Atlantic Forest biome.